Assess the knowledge about new-born care among the primi mothers at a selected hospital, Vadodara, Gujarat (Journal of Pharmaceutical Negative Results, 2022)
Introduction: The postnatal period has been termed as fourth stage of labour. It has three distinct but continuous phases.1 postnatal period begins after the third stage of labour and includes first six weeks after delivery. During this time women’s reproductive organs gradually returns to the normal size and shape. Postnatal period is a crucial period in woman’s life and lot of physiological changes used to occur. They are in need of special care during pregnancy, at the time of labour as well as after delivery of child in order to prove safe motherhood and healthy living. The postnatal period is a critical transitional time for a woman and her new born physiologically, emotionally, and socially.2 postnatal mothers used to have physical and emotional discomforts, lack of sleep due to new born baby, visitors, noise, and discomfort with episiotomy. Due to child birth, mother becomes tired and weak. However, taking care of hygiene is also important for all postnatal mothers. Hygiene includes self care as well menstrual careMethod: The Parul Sevashram Hospital in Vadodara served as the study's location. A practical simple random sampling procedure was used to select 60 primi mothers in total. Multiple choice questions and a checklist were included in the questionnaire used to gather the data. Age, religion, degree of education, place of residence, and other socio-demographic characteristics were taken into account when formulating the questions. For this examination, a quantitative descriptive research design was adopted.Results: In this study, the majority of participants, Regarding age of the mother 11(22%) are the age group of 18-25 years, followed by in the age group of 26-30 years17(34%) and most of them were in the age group of 31-36 years 22(44%), no mother belongs to the age group of 36 and above. The results indicated that age of the mother and educational status are significant at the p0.05 level, socio-demographic variables like the mother's age, residence, employment status, family monthly income, marital status, family type, parity are not significant at that level.Conclusion: It is important to give primi mothers regarding newborn care knowledge and practice after delivering the planned teaching programme.